Pemikiran Al-Khawarizmi dalam Meletakkan Dasar Pengembangan Ilmu Astronomi Islam - Mulyadi, Achmad (Universitas Islam Negeri (UIN) Walisongo Semarang, Indonesia, 2018)
The progress of Islamic civilization is inseparable from the influence of the emergence and rapid development of Islamic astronomy. Islam leads the world civilization and breaks the record as the longest-running civilization lasting more than 14 centuries. At this time, astronomical activities in the Islamic world began to develop intensively. This condition cannot be separated from the role of al-Khwarizmi who made a very valuable contribution. The construction of his thinking which was based on mathematical astronomy made him the foundation of the development of Islamic astronomy, in addition to its development of the geocentric theory of Aristotle and Ptolemy. This is the real contribution of al-Khwarizmi that is very large and fundamental in the heyday of medieval Islam which eventually became the starting point of the scientific development and subsequent Muslim astronomers to date. The emergence of various observatories and planetariums which made observations with more modern tools finally gave birth to many new theories in the study of world astronomy. This study explores al-Khwarizmi's role in the growth and development of astronomy in his time to the present.